2022
DOI: 10.1091/mbc.e21-11-0589
|View full text |Cite
|
Sign up to set email alerts
|

Load adaptation by endocytic actin networks

Abstract: Clathrin-mediated endocytosis (CME) robustness under elevated membrane tension is maintained by actin assembly-mediated force generation. However, whether more actin assembles at endocytic sites in response to increased load has not previously been investigated. Here actin network ultrastructure at CME sites was examined under low and high membrane tension. Actin and N-WASP spatial organization indicate that actin polymerization initiates at the base of clathrin-coated pits and that the network then grows away… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 91 publications
3
17
0
Order By: Relevance
“…It was previously shown that the inward movement of endocytic CCPs during their internalization is dependent on actin polymerization (Ferguson et al ., 2017). Moreover, it has been shown that actin-driven displacement of clathrin coats (away from the cell surface) gets longer with increasing membrane tension (Ferguson et al ., 2017), in accord with models suggesting that actin polymerization pushing the clathrin coats increases with the increasing mechanical load (Kaplan et al ., 2022).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…It was previously shown that the inward movement of endocytic CCPs during their internalization is dependent on actin polymerization (Ferguson et al ., 2017). Moreover, it has been shown that actin-driven displacement of clathrin coats (away from the cell surface) gets longer with increasing membrane tension (Ferguson et al ., 2017), in accord with models suggesting that actin polymerization pushing the clathrin coats increases with the increasing mechanical load (Kaplan et al ., 2022).…”
Section: Resultssupporting
confidence: 82%
“…Moreover, it has been shown that actin-driven displacement of clathrin coats (away from the cell surface) gets longer with increasing membrane tension (Ferguson et al, 2017), in accord with models suggesting that actin polymerization pushing the clathrin coats increases with the increasing mechanical load (Kaplan et al, 2022).…”
Section: Results: Formation and Internalization Of Canonical Clathrin...supporting
confidence: 71%
See 3 more Smart Citations